Composition and biological activities of seaweed in coastal waters of Bintulu, Sarawak, Malaysia - Zawawi, Mohd Hafizbillah (2014)
Seaweed communities are considered as important component in the coastal ecosystems and able to produce a great variety of secondary metabolites for biological activities. The coastline of Bintulu geographically surrounded by rocky shore areas and some reef areas provide favorable natural habitat for seaweed communities. Rapid development and anthropogenic disturbance near the shorelines may give negative effect to the organism in the coastal ecology and some seaweed species might have great potential for biological activities. However, no clear information was reported on seaweed distribution and status of seaweed species from the Bintulu coastal waters and none of the study reported on potential of seaweed species for biological activities. Therefore a study was conducted to determine the species composition of seaweed communities from Bintulu coastal waters and to determine the antioxidant and antimicrobial activities of dominant seaweed species. A total of 54 species of seaweeds were identified from six different study areas of Bintulu coast by using NaGISA Protocol; in which 23 species were from Rhodophyta (11 families), 15 species were from Phaeophyta (2 families) and 16 species were from Chlorophyta (10 families). The abundance of seaweeds was high in the rocky substrate, while Rhodophyta (11 families and 23 species) was the common and highest group of seaweeds found in this coastal area. This study recorded 12 species of seaweeds which can be commonly found in Bintulu coastal waters (Chaetomorpha sp., Ulva intestinalis, Padina minor, Padina australis, Gracilaria salicornia, Hydropuntia edulis, Hypnea cervicornis, Hypnea spicifera, Acanthophora spicifera, Laurencia sp., Chondrophycus papillosus and Laurencia similis). Interestingly, the present study recorded high numbers of seaweed species when compared to the previous studies conducted at Bintulu, Sarawak and most of the new species recorded from fringing reef area. The extracts obtained from 20 species of seaweeds were evaluated for their antioxidant and antimicrobial activities. Antioxidant properties from methanolic extracts were evaluated according to the total phenolic contents by using Folin-Ciocalteau method and free radical scavenging activity determined by standard 2, 2-Diphenyl-1-picrylhydrazyl (DPPH). High level of antioxidant properties was recorded from Lobophora variegata, Padina boryana and Acanthophora spicifera. Both Lobophora variegata and Padina boryana showed greater antioxidant properties than the control. There was high correlation between concentration of phenolic contents and antioxidant properties by the DPPH scavenging activity. Antimicrobial activity was examined using disc diffusion method. The samples were subjected to solvent extraction using chloroform, acetone, methanol and ethanol. Maximum inhibition activities were shown from crude extract of Chaetomorpha sp. and Chaetomorpha antennina. Both chloroform crude extract of Chaetomorpha antennina and acetone crude extract of Chaetomorpha sp. showed greater antibacterial activities than the control against Streptococcus gallolyticus. Present study recorded no correlation between antimicrobial and antioxidant activities. Bintulu coastal waters are abounding in seaweed species which provided suitable environment for the marine ecology and present study recorded some seaweed species contain potential active compounds for antimicrobial activities and antioxidant properties. Therefore, study recommended for further monitoring on the seaweed diversity and isolates the active compounds from the high potential seaweed species.